2017
DOI: 10.30699/ics.journal.01.23
|View full text |Cite
|
Sign up to set email alerts
|

Silane/Siloxane Surface Treatment for Cohesion Ability and Strengthening Agent of Historical Stone

Abstract: Ir Cons Sci J 2017; 1(1): [23][24][25][26][27][28][29][30][31] Silane/siloxane surface treatment are proposed as potential polymeric materials for protective and consolidation coatings of limestone substrates. The silane and silioxane coatings are widely used to strengthen and waterproof of historical monuments. Historical stones are very fragile because of bearing many years in sever weathering conditions. Strengthening historical stones requires paying attention to surface treatment by the aim of decreasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Therefore, further efforts were focused on copolymers or blends from both acrylic and fluorinated polymers (Mazzola et al, 2003;Malshe and Sangaj, 2009). Furthermore, silanes and siloxanes (Tsakalof et al, 2007;Vacchiano et al, 2008;Ershad-Langroudi et al, 2017) also showed interesting properties in terms of impermeability and protection against color loss, although these were strongly dependent on the specific substrate. Polymers from cellulose have been extensively used and studied for application on cultural heritage, finding that both cellulose ethers (Feller and Wilt, 1990) and nitrate (Selwitz, 1988) have some stability issues.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further efforts were focused on copolymers or blends from both acrylic and fluorinated polymers (Mazzola et al, 2003;Malshe and Sangaj, 2009). Furthermore, silanes and siloxanes (Tsakalof et al, 2007;Vacchiano et al, 2008;Ershad-Langroudi et al, 2017) also showed interesting properties in terms of impermeability and protection against color loss, although these were strongly dependent on the specific substrate. Polymers from cellulose have been extensively used and studied for application on cultural heritage, finding that both cellulose ethers (Feller and Wilt, 1990) and nitrate (Selwitz, 1988) have some stability issues.…”
Section: Introductionmentioning
confidence: 99%
“…The impregnation of the limestone surface with 3-MPTMS showed a film coating similar to the impregnated travertine surface ( Figure 8 c), with gel formation and attached to both stone surfaces, as noticed for the different impregnation of treated stone [ 29 , 52 , 53 , 54 ]. Comparing SEM images obtained for the two types of stones showed that depending on the structure of the stones, the coupling agent should be chosen [ 14 , 28 ]. Both coupling agents showed that they modify the surface, and this can be correlated with the FTIR microscopy, too.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption of the coupling agent depends on the stone structure, and coupling agents thus facilitate the formation of a film as a crust or can penetrate easily the porous surface of certain stones [ 24 ]. Based on these observations, it can be concluded that silanization leads to a rough surface, which theoretically can enhance the bacterial colonization, but hopefully, the combination of the coupling agent and silver nanoparticles will lead to a resistant surface against biofilm formation [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations